A new resin with improved processability and thermal stability. (February 2017) - Sheng, Liping; Zeng, Jingcheng; Xing, Suli; Yin, Changping; Yang, Jinshui; Yang, Yudong; Xiao, Jiayu
To maintain outstanding thermal stability, amino- and hydroxyl-containing phthalonitrile monomers, 4-(4-aminophenoxy)-phthalonitrile (APN) and 4-(4-hydroxyphenoxy)-phthalonitrile (HPN) were selected and synthesized. Their structures were confirmed by proton nuclear magnetic resonance spectroscopy. Their curing polymers were characterized by Fourier transform infrared spectroscopy. The self-catalytic curing behaviors of the monomers were investigated by differential scanning calorimetry (DSC) at different heating rates. From the results, APN exhibits a higher curing temperature, while HPN exhibits a longer curing time. Then, mixtures of these monomers were investigated by DSC. The result shows that the 50/50 mixture exhibits different autocatalytic behaviors: the curing temperature is lower than that of APN and the curing time of the mixture is shorter than that of HPN. Furthermore, thermogravimetric analysis shows that the polymer from the mixture exhibits higher temperature of 5% weight loss ( T 5% ) and char yield value at 800°C than those of the polymers from each monomer. All these results indicate that the new mixture resin exhibits improved processability with excellent thermal stability, attributed to the synergistic effect between similar monomers; the synergistic effect optimizes the cure reaction kinetics and promotes cross-linking reactions, thereby producing an excellent resin; this approach is a new method for improving the processability without sacrificing thermal stability.